Levels of trace minerals, glucose and haemoglobin in relation to occurrence of post-parturient oestrum in buffaloes - SINGH, ANAND; SAXENA, M S; PRASAD, J K (The Indian Journal of Animal Reproduction, 2023)
The study was conducted to study the role of plasma/blood levels of copper, zinc, cobalt, glucose and haemoglobin in relation to early or late occurrence of post-partum oestrus in buffaloes. The mean levels of plasma copper, zinc, cobalt, glucose and blood haemoglobin (average of levels at day 0, 30 and 60) were 1.125±0.024 μg/ml, 1.484±0.029 μg/ml, 0.541±0.024 μg/ml, 52.49±1.382 mg% and 13.29±0.209 g% and 1.209±0.026 μg/ml, 1.472±0.031 μg/ml, 0.477±0.020 μg/ml, 53.82±1.744 mg% and 13.63±0.256 g%, respectively, in buffaloes of Group I (oestrum in> 90 days, n = 10) and Group - 2 (oestrum in< 90 days, n = 6). The t-test analysis revealed that the levels of copper, zinc, cobalt, glucose and haemoglobin were not related to early or late occurrence of post-partum oestrum in buffaloes.